Outdoor games – an effective means of developing physical qualities of junior schoolchildren - Polevoy G.G.; Egorycheva E.V.; Fedorov A.V.; Ardigò L.P. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the impact of outdoor games at school on the physical fitness indicators of 8-9 year old children. Methods and structure of the study. The pedagogical experiment was carried out from September 12, 2022 to May 17, 2023 on the basis of school No. 12 in Kirov, 56 schoolchildren from the 2nd grade took part in it, who were differentiated into two groups: control (CG) and experimental (EG) 28 students each. In the EG, in contrast to the CG, along with traditional classes, outdoor games were used for 8-9 minutes in each physical education lesson. Results and conclusions. As a result of the use of outdoor games in the EG, a significant increase in indicators was revealed for all tests: “Running 30 meters” - an improvement of 18.2% (p<0.05); “Pulling up from a lying position” – improvement by 40.2% (p<0.05); “Shuttle run 3x10 m” – improvement by 10.3% (p<0.05); “Forward bend” – improvement by 43.2% (p<0.05). The results of the pedagogical experiment showed that outdoor games are an effective means of increasing the physical activity of students in a general education organization.